2019
DOI: 10.1002/jbm.a.36807
|View full text |Cite
|
Sign up to set email alerts
|

Nanofilm generated non‐pharmacological anabolic bone stimulus

Abstract: Stimulus-responsive nanomaterials have mainly been employed to ablate or destroy tissues or to facilitate controlled release of drugs or biologics. Herein, we demonstrate the potential of stimulus-responsive nanomaterials to promote tissue regeneration via a non-pharmacological and noninvasive strategy. Thin nanofilms of an optically-absorbing organic dye or nanoparticle (single-walled graphene nanoribbons[SWOGNR]) were placed over (without touching the skin) a rodent femoral fracture site. A nanosecond pulsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition, it has been indicated that GDs could be applied to real-time detection of bone repair process. After GDs were modified with functional groups or combined with fluorescent/magnetic molecules, the imaging efficiency of the GDs-containing composites with various detection equipment such as computed tomography (CT), 48 ultrasound 49 and nuclear magnetic resonance (NMR) 50 could be significantly improved, by which the structural integrity, 51 tumorigenicity, 52 degradability 53 and mineralization 54 of the composites could be real-timely evaluated, which was definitely helpful for further and deeper study of the bone repair process. Compared with most of other substrate contrast agents, GDs could be more conducive to the quantitative control of loaded fluorescent markers or paramagnetic substances 55 based on their excellent conductivity and large SSA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been indicated that GDs could be applied to real-time detection of bone repair process. After GDs were modified with functional groups or combined with fluorescent/magnetic molecules, the imaging efficiency of the GDs-containing composites with various detection equipment such as computed tomography (CT), 48 ultrasound 49 and nuclear magnetic resonance (NMR) 50 could be significantly improved, by which the structural integrity, 51 tumorigenicity, 52 degradability 53 and mineralization 54 of the composites could be real-timely evaluated, which was definitely helpful for further and deeper study of the bone repair process. Compared with most of other substrate contrast agents, GDs could be more conducive to the quantitative control of loaded fluorescent markers or paramagnetic substances 55 based on their excellent conductivity and large SSA.…”
Section: Introductionmentioning
confidence: 99%
“…[ 238 , 239 , 240 ] In addition, the low‐power NIR facilitates wound healing, bone repair, angiogenesis, etc. [ 241 , 242 , 243 ] In this process, the PTAs with high photothermal conversion efficiency exert the largest agglomerative thermal effect, to achieve a fixed‐point temperature rise and then heat the tumor, while the normal tissue is not damaged by heat. Therefore, the photothermal conversion efficiency of PTAs is very important.…”
Section: Discussionmentioning
confidence: 99%
“…The photocurrent upon two photon excitation of this small sized C 3 N 4 sheet would induce a charge transfer and increased cytosolic Ca 2+ accumulation, resulting in enhanced osteogenic differentiation of stem cells and new bone formation. In addition, single‑walled graphene nanoribbons have been reported to generate photoacoustic signals under 905 nm NIR laser radiation, which could serve as an anabolic stimulus for noninvasive bone defect repair in a rodent femoral fracture site 103 .…”
Section: Discussionmentioning
confidence: 99%